Ode to the Heart Smaller than a Pencil Eraser - Igloria, Luisa A., 1961- (Book collections on Project MUSE., 2014)
"When Luisa Igloria cites Epictetus-'as soon as a thing has been seen, it is carried away, and another comes in its place'-she introduces the crowded and contradictory world her poems portray: a realm of transience, yes, where the vulnerable come to harm and everything disappears, but also a scene of tremendous, unpredictable bounty, the gloriously hued density this poet loves to detail. 'I was raised / to believe not only the beautiful can live on / Parnassus, ' she tells us, and she makes it true, by including in the cyclonic swirl of her poems practically everything: a gorgeous, trou